2007
DOI: 10.1038/nature06129
|View full text |Cite
|
Sign up to set email alerts
|

Generation of functional multipotent adult stem cells from GPR125+ germline progenitors

Abstract: Adult mammalian testis is a source of pluripotent stem cells. However, the lack of specific surface markers has hampered identification and tracking of the unrecognized subset of germ cells that gives rise to multipotent cells. Although embryonic-like cells can be derived from adult testis cultures after only several weeks in vitro, it is not known whether adult self-renewing spermatogonia in long-term culture can generate such stem cells as well. Here, we show that highly proliferative adult spermatogonial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
376
1
4

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 399 publications
(397 citation statements)
references
References 30 publications
16
376
1
4
Order By: Relevance
“…These cells exhibit a chimera formation efficiency of only 22%, express low levels of Rex1, Stra8, and Dazl, and express high levels of brachyury and Nog (Seandel et al, 2007). Earlier reports by Kanatsu-Shinohara et al (2004) and Guan et al (2006) clearly indicate that both ES-like and EpiSC-like colonies appear during derivation.…”
Section: Choice Of Pluripotent Statesmentioning
confidence: 86%
See 4 more Smart Citations
“…These cells exhibit a chimera formation efficiency of only 22%, express low levels of Rex1, Stra8, and Dazl, and express high levels of brachyury and Nog (Seandel et al, 2007). Earlier reports by Kanatsu-Shinohara et al (2004) and Guan et al (2006) clearly indicate that both ES-like and EpiSC-like colonies appear during derivation.…”
Section: Choice Of Pluripotent Statesmentioning
confidence: 86%
“…mGSs showed very similar morphology and gene expression patterns to mouse ES cells, and deve-loped into all 3 germ layers both in vitro and in vivo and contributed to chimera formation. Subsequent experiments showed that mGSs could also be derived from adult mice with various genetic backgrounds (Guan et al, 2006;Seandel et al, 2007). Clonal analysis in a separate experiment confirmed that they originated from SSCs (Ko et al, 2009).…”
Section: Dedifferentiation Of Germline Stem Cells Into Pluripotent Stmentioning
confidence: 92%
See 3 more Smart Citations